Can Experience Determine the Adoption of Industrial Revolution 4.0 Skills in 21st Century Mathematics Education? - Musa Adekunle Ayanwale (Research in Social Sciences and Technology- OpenED Network, 2023)
Teachers in secondary schools were studied to determine their readiness to adopt fourth industrial revolution (4IR) technologies to enhance their teaching practices and student learning. Through Industry 4.0, technologies are also becoming available as products for education, transforming the rules and norms of education. Secondary school mathematics teachers in Nigeria must prepare themselves to embrace digital skills so that they will be ready for new teaching and learning processes that are being introduced by these new digital tools. In this study, a cross-sectional quantitative approach was used. The data were collected using a self-developed instrument with a content validity index of 0.96 and a MacDonald Omega reliability index of 0.84. A purposive sampling technique was used to select 211 mathematics teachers in three Lagos State education districts. Analyses of the obtained data were performed using descriptive statistics and ANOVA at a significance level of 0.05. Results indicate that mathematics teachers are ready to integrate 4IR skills and emerging technologies into their classrooms. In addition, the willingness of participants to adopt relevant 4IR skills across their years of experience was statistically significant. A new path is charted for school administrators, mathematics teachers, and stakeholders in the education sector to assist in policy design toward 4IR, thereby contributing to the existing literature on adopting emerging technologies to teach mathematics education in sub-Saharan Africa.